Enhancing Teachers' Self-Confidence, Work Motivation, and Social Attitudes Through Character-Strengthening In-House Training - Yosef Wao Werang; Victor Novianto; Esti Setiawati (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to improve teachers' self-confidence, work motivation, and social attitudes through character-strengthening In-House Training (IHT) at SD Inpres 01 Pamaha, Arfak Mountains Regency, West Papua. The novelty of this study lies in the integration of character-based training within an IHT model applied contextually in a 3T (frontier, outermost, and disadvantaged) region, together with a simultaneous focus on improving three psychosocial dimensions of teachers. The study employed a School Action Research (SAR) design using the Kemmis and McTaggart spiral cycle model, which comprises planning, action, observation, and reflection stages carried out over two cycles. The subjects were eight teachers. Data were collected through questionnaires, observation, and documentation, and analyzed using a descriptive quantitative approach with percentage techniques. The results show significant improvement across all three aspects examined. Teachers' self-confidence rose from the sufficient category (75.0%) in Cycle I to the high (87.5%) and very high (12.5%) categories in Cycle II. Work motivation improved from the sufficient category (87.5%) to the high (75.0%) and very high (25.0%) categories. Social attitudes likewise improved from the sufficient category (62.5%) to the high (87.5%) and very high (12.5%) categories. The findings indicate that character-strengthening IHT is effective in improving teachers' psychosocial aspects and holds potential as a professional development strategy for teachers in 3T regions.